2000
DOI: 10.1614/0043-1745(2000)048[0089:eogosm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glyphosate on soil microbial activity and biomass

Abstract: Herbicides applied to soils potentially affect soil microbial activity. Quantity and frequency of glyphosate application have escalated with the advent of glyphosate-tolerant crops. The objective of this study was to determine the effect of increasing glyphosate application rate on soil microbial biomass and activity. The soil used was Weswood silt loam. The isopropylamine salt of glyphosate was added at rates of 47, 94, 140, and 234 µg ai g−1 soil based on an assumed 2-mm glyphosate–soil interaction depth. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
142
4
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(173 citation statements)
references
References 15 publications
15
142
4
12
Order By: Relevance
“…Besides its biological degradation in soil and water, at least transiently, glyphosate also stimulates the soil basal respiration, increases the microbial biomass (Wardle et al, 1994;Haney et al, 2000), and reduces the growth of earthworms after repeated applications (Springett & Gray, 1992). Souza et al (1999aSouza et al ( , 1999b verified that glyphosate leaching was very small in two different Brazilian soils and the soil microorganisms used the herbicide as C source, but the process was extremely dependent of soil moisture.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Besides its biological degradation in soil and water, at least transiently, glyphosate also stimulates the soil basal respiration, increases the microbial biomass (Wardle et al, 1994;Haney et al, 2000), and reduces the growth of earthworms after repeated applications (Springett & Gray, 1992). Souza et al (1999aSouza et al ( , 1999b verified that glyphosate leaching was very small in two different Brazilian soils and the soil microorganisms used the herbicide as C source, but the process was extremely dependent of soil moisture.…”
Section: Introductionmentioning
confidence: 93%
“…Nowadays it is one of the most popular herbicides not only in agriculture but also in forestry, because of its effective control of competitive vegetation and low mammalian toxicity (Busse et al, 2001). It acts by enzymatic inhibition of the shikimic acid pathway, resulting in depletion of essential aromatic amino acids needed for plant growing and survival (Haney et al, 2000;Environmental Protection Agency, 2003). Most living organisms do not have this enzyme, which is however, ubiquitous in microorganisms (Busse et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in the present study trifluralin, glyphosate and ametrin affected microbial activity, this effect was only observed over a short period of time, a fact not sufficient to consider these products toxic to the fungus. Haney et al (2000) concluded that glyphosate seems to be rapidly and directly degraded by soil microorganisms. In another study (Haney et al 2002), these authors demonstrated that the product significantly stimulated soil microbial activity and biomass, in addition to being easily degraded irrespective of the amount of organic matter or soil type.…”
mentioning
confidence: 99%